Changes in the thigh and arm muscle glycogen contents in Japanese male gymnasts during normal practice - Kamei, A.; Hasegawa, H.; Takahashi, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
To systematically examine the optimal carbohydrate intake of elite athletes who perform high intensity practice every day, it is necessary to investigate muscle glycogen changes before and after practice to determine the amount of consumption during normal practice. In this study, we measured the muscle glycogen concentrations in thigh and upper arm muscles, and investigated the muscle glycogen changes during daily practice for two male gymnasts. Two male gymnasts (Player A and Player B) participating in an international competition were recruited for this study. The study was conducted during training camp. The glycogen contents of the thigh muscle group (the vastus lateralis and vastus intermedius muscles) of the right leg and biceps brachii muscle of the right arm were measured by carbon magnetic resonance spectroscopy. Measurements were performed three times: before the morning practice, after the afternoon practice, and before the morning practice on the following day. Body weight and body composition were measured concurrently with the three measurements of muscle glycogen concentrations. Body composition was measured using the impedance method. Meals and supplements were ingested freely during the study, and all foods and drinks were recorded. The practice routines were recorded by the investigator. To calculate energy consumption, physical activity metabolic equivalent values were determined by factor addition from practice records. The first body weight and body fat percentage were 52.6 kg, 9.7% for Player A and 61.1 kg, 10% for Player B. The carbohydrate intake per body weight was 5.6 g/kg body weight for Player A and 6.8 g/kg body weight for Player B. Assuming that the muscle glycogen concentration in the first measurement was 100%, the muscle glycogen concentration of the thigh in the third measurement increased by 12.4% for Player A and 25.3% for Player B. Conversely, in the biceps, muscle glycogen concentrations decreased by 8.7% and 3.4% in Players A and B, respectively. Thus, the thigh and arm muscles showed different changes in muscle glycogen. In conclusion, when assessing the optimal carbohydrate intake from the evaluation of muscle glycogen changes during normal practice in male gymnasts, we propose combined measurement of the thigh and arm.